Enhancing 5‐aminolevulinic acid tolerance and production by engineering the antioxidant defense system of Escherichia coli. Issue 8 (17th April 2019) - Zhu, Chengchao; Chen, Jiuzhou; Wang, Yu; Wang, Lixian; Guo, Xuan; Chen, Ning; Zheng, Ping; Sun, Jibin; Ma, Yanhe
Abstract: 5‐Aminolevulinic acid (ALA) is a value‐added compound with potential applications in the fields of agriculture and medicine. Although massive efforts have recently been devoted to building microbial producers of ALA through metabolic engineering, few studies focused on the cellular response and tolerance to ALA. In this study, we demonstrated that ALA caused severe cell damage and morphology change of Escherichia coli via generating reactive oxygen species (ROS), which were further determined to be mainly hydrogen peroxide and superoxide anion radical. ALA treatment activated the native antioxidant defense system by upregulating catalase (CAT) and superoxide dismutase (SOD) expression to combat ROS. Further overexpressing CAT (encoded by katG and katE ) and SOD (encoded by sodA, sodB, and sodC ) not only improved ALA tolerance but also its production level. Notably, coexpression of katE and sodB in an ALA synthase expressing strain enhanced the biomass and final ALA titer by 81% and 117% (11.5 g/L) in a 5 L bioreactor, respectively. This study demonstrates the importance of tolerance engineering in strain development. Reinforcing the antioxidant defense system holds promise to improve the bioproduction of chemicals that cause oxidative stress. Abstract : 5‐Aminolevulinic acid (ALA) is a value‐added compound with potential applications in the fields of agriculture and medicine. Although massive efforts have recently been devoted to building microbial producers of ALA through metabolic engineering, few studies focused on the cellular response and tolerance to ALA.